Primary ciliogenesis is a crucial step for multiciliated cell determinism in the respiratory epithelium. Issue 15 (25th June 2021) - Belgacemi, Randa; Diabasana, Zania; Hoarau, Antony; Dubernard, Xavier; Mérol, Jean‐Claude; Ruaux, Christophe; Polette, Myriam; Perotin, Jeanne‐Marie; Deslée, Gaëtan; Dormoy, Valérian
Abstract: The alteration of the mucociliary clearance is a major hallmark of respiratory diseases related to structural and functional cilia abnormalities such as chronic obstructive pulmonary diseases (COPD), asthma and cystic fibrosis. Primary cilia and motile cilia are the two principal organelles involved in the control of cell fate in the airways. We tested the effect of primary cilia removal in the establishment of a fully differentiated respiratory epithelium. Epithelial barrier integrity was not altered while multiciliated cells were decreased and mucous‐secreting cells were increased. Primary cilia homeostasis is therefore paramount for airway epithelial cell differentiation. Primary cilia‐associated pathophysiologic implications require further investigations in the context of respiratory diseases.